2018
DOI: 10.1080/14397595.2018.1480256
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between YKL-40 and pulmonary arterial hypertension in systemic sclerosis

Abstract: A higher YKL-40 level with PAH may be reflective of angiogenesis due to capillary injury in SSc. YKL-40 may offer a useful and easily applicable diagnostic biomarker of SSc complicated with PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Our finding of increased serum YKL-40 concentrations in IPF compared with controls is in complete agreement with the previous clinical research studies in the ILD field reporting elevated YKL-40 concentrations in serum and/or BALf of patients with IPF (27)(28)(29)(30), sarcoidosis (44,45), or connective tissue disease-associated ILD (CTD-ILD) (29,(46)(47)(48)(49). It has been also shown that high serum and BALf YKL-40 concentrations are associated with poor survival in patients with IPF and hypersensitivity pneumonitis (HP) (28,30).…”
Section: Longitudinal Changes Insupporting
confidence: 92%
“…Our finding of increased serum YKL-40 concentrations in IPF compared with controls is in complete agreement with the previous clinical research studies in the ILD field reporting elevated YKL-40 concentrations in serum and/or BALf of patients with IPF (27)(28)(29)(30), sarcoidosis (44,45), or connective tissue disease-associated ILD (CTD-ILD) (29,(46)(47)(48)(49). It has been also shown that high serum and BALf YKL-40 concentrations are associated with poor survival in patients with IPF and hypersensitivity pneumonitis (HP) (28,30).…”
Section: Longitudinal Changes Insupporting
confidence: 92%
“…Previous studies have identified CHI3L1 as an indicator of disease severity and prognosis in patients with IPAH (21), PAH associated with scleroderma (22), and IPF (19), but the mechanism of CHI3L1 in the pathogenesis of PH has not been investigated. The importance of CHI3L1induced responses can be seen in the large number of diseases characterized by inflammation and remodeling in which CHI3L1 excess has been documented (52)(53)(54)(55)(56)(57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a cohort of 64 IPF patients and 42 age-matched controls, CHI3L1 levels were elevated in patients with IPF, and high levels of CHI3L1 are associated with severe disease progression as defined by lung transplantation or death ( Zhou et al, 2014 ). Since then, numerus studies have showed that the serum CHI3L1 levels are increased in patients with other types of ILD, including connective tissue-related ILD ( Hozumi et al, 2017 ; Furukawa et al, 2019 ; Jiang et al, 2019 ), sarcoidosis ( Johansen et al, 2005 ; Kruit et al, 2007 ), cryptogenic tissue pneumonia ( Korthagen et al, 2014 ; Long et al, 2017 ), asbestosis-ILD ( Väänänen et al, 2017 ), and idiopathic nonspecific interstitial ( Korthagen et al, 2014 ; Long et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%